Study of the Effect of NaOH Type Alkaline Catalyst on the Physicochemical Characteristics of Used Cooking Oil Biodiesel - Dani, Dani Hari Tunggal Prasetiyo; Ilminnafik, Nasrul; Trifiananto, Muhammad; Sanata, Andi; Muhammad, Alief (PERTETA, 2024)
Dependence on fossil fuels causes significant environmental damage and increases costs and scarcity in the future. To overcome this problem, a transition to renewable energy is needed, one of which is biodiesel which can be obtained from used cooking oil. This study aims to convert used cooking oil that cannot be reused into biodiesel products. Biodiesel synthesis can be carried out by the transesterification process, using NaOH catalyst with concentration variations of 0.5%, 0.75%, 1%, 1.25%, and 1.5% of the total mass of oil. The test parameters are calorific value, density, viscosity and flash point as well as yield on used cooking oil biodiesel products. The test results show that the use of a catalyst concentration of 1% produces more optimal density, viscosity, and calorific value and flash point. Each value is 0.859 g / cm³, 2.34 cSt, 10,356 cal / g, and 139°C. However, the use of a catalyst concentration of 0.5% shows that the biodiesel product is less than optimal. This can be shown by the highest density, viscosity and flash point values of the catalyst concentration variations used. Each value is 0.88 g/cm3, 3.16 cSt and 178°C, while the calorific value is also low with a value of 9,689 cal/g. However, when viewed from the yield, the catalyst concentration of 0.5% produces the highest value of all catalyst concentration variations used with a value of 88%.